History of safety in Iranian construction industry - Keyvan Zandiye; Roohollah Taherkhani; Reza Ziaie Moayed (مهندسی و مدیریت ساخت)
The safety issue has always been remarkably respected by researchers for the history of accidents in the construction industry, and many studies have been conducted on various safety related issues. Issues such as: the introduction of safety standards, the assessment of standards and safety regulations and their adaptation to the current situation in the country, the assessment of safety in different ways by providing models and frameworks for use in future projects and environmental safety factors have taken. The diversity and scope of studies on safety issues with different subjects has made it necessary to provide a literature review in this regard, which will facilitate access to information on various safety categories in the construction industry for researchers in the future. Therefore, in this article, a literature review of existing articles on safety in the construction industry has been carried out in Persian articles. The division of subjects into existing safety research can be divided into three categories: the first group has been introduced into the safety issue from the perspective of safety management; for example, safety assessment and safety planning fall into this category. The second group features individual and group factors For example, workers' attitudes and attitudes, worker's attitudes and environmental safety factors can be addressed in this study; the third group also addresses issues related to safety, health and the environment. Eventually, these papers were reviewed at various times. 2 The important findings of the research include: research on safety in construction, and the issues and issues of safety research in the construction industry, which tends to work at their peak. In the final step, there are three existing vacancies that should be explored further.